On the economic impacts of COVID-19: A text mining literature analysis - Gonçalves, H.; Moro, S. (Review of Development Economics, 2023)
The COVID-19 outbreak has affected everyday lives worldwide. As governments started to implement confinement and businesses closure measures, the economic impact immediately was felt by entire societies. The urgency of such theme has led researchers to study the phenomenon. Accordingly, the purpose of this research is to provide the state of the art on relevant dimensions and hot topics of research to understand the economic impacts of COVID-19. In this survey, we conduct a text mining analysis of 301 articles published during 2020 which analysed such economic impacts. By defining a set of relevant dimensions grounded on existing literature, we were able to extract a set of coherent topics that aggregate the collected articles, characterised by the predominance of a few sets of dimensions. We found that the impact on “financial markets” was widely studied, especially in relation to Asia. Next, we found a more diverse range of themes analysed in Europe, from “government measures” to “macroeconomic variables”. We also discovered that America has not received the same degree of attention, and “institutions”, “Africa” or “other pandemics” was less studied. We anticipate that future research will proliferate focusing on several themes, from environmental issues to the effectiveness of government measures.